AN ANALYSIS OF THE PREVALENCE OF POLYPHARMACY AMONG INPATIENTS OF A TERTIARY CARE HOSPITAL IN KERALA - SHAJAHAN, JIHANA; P, ABDUL ASLAM; JOY, JOBIN; BABY, MINU (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The aim of the study was to estimate the prevalence of polypharmacy, identify the age groups commonly associated with polypharmacy, study the correlation between duration of hospital stay and polypharmacy, and identify the diseases commonly associated with polypharmacy Methods: Record-based, prospective, and cross-sectional study among 370 inpatients of a tertiary care hospital in Kerala. Prescriptions containing ≥3 drugs were collected from inpatient medical records of patients with at least 3 days hospital stay. The number of drugs ≥5 was considered as polypharmacy in the present study. Results: The prevalence of polypharmacy was 93% and average the number of drugs per prescription was 8.81±3.097. Average number of drugs per prescription was significantly high among patients >60 years. Percentage of prescriptions with polypharmacy among patients with duration of stay 3–5 days, 6–8 days, and ≥ 9 days was found to be 89.4, 98.6, and 100, respectively. There was a significant positive association between duration of hospital stay and percentage of prescriptions with polypharmacy as well as average number of drugs per prescription. Diseases or comorbidities most commonly associated with polypharmacy were hypertension, diabetes mellitus, cerebrovascular accidents, coronary artery disease, and dyslipidemia. Conclusion: The prevalence of polypharmacy was high in the present study (93%) when compared to similar studies. Age >60 years was strongly associated with the prevalence of polypharmacy, but gender was not found to be factor. Duration of hospital stay was an important factor positively associated with percentage of prescriptions with polypharmacy as well as number of drugs per prescription.